Sports de nature et décentralisation - Ludovic Falaix (Développement Durable et Territoires)
After over a decade of practice for the authority concerning the outdoors sports, which was entrusted to the departments, only twenty-eight of the latter have a PDESI at their disposal. The PDESI, which stands for the Department Program for Territories, Sites and Itineraries, is a plan for the territorial designing and local development, which is created by the CDESI, i.e. the Department Committee for Territories, Sites and Itineraries. This article investigates the form of decentralization of this authority concerning the outdoors sports, whose public policies frame of reference is decided on by the state government. Starting from the analysis of a questionnaire submitted to the departmental councils, we are considering the socio-territorial modes of organization that are required for the implementation of the “controlled development of the outdoors sports” stated by the government. As for the critical inspection of the institutional documentation, our purpose is to disclose the legislators’ intents when having the sports practice territories accessible, induced by the registration of the territories, the sites and the itineraries (ESI) in the PDESI. Eventually, this article endeavours to question the relevance of a prescriptive plan such as the PDESI, on the one hand, in order to reinforce the scientific knowledge related to the issue of the territorialized public action as far as sports are concerned, and on the other hand to examine the cultural characteristics of the outdoors sports and recreational practices.